How high-tech entrepreneurial ventures cope with the global crisis: changes in product innovation and internationalization strategies. Issue 7 (2nd October 2016) - Colombo, Massimo G.; Piva, Evila; Quas, Anita; Rossi-Lamastra, Cristina
Abstract: The global crisis that began in the second half of 2008 abruptly changed the business context, inducing firms to react by modifying their strategies. This paper examines changes in innovation and internationalization strategies that high-tech entrepreneurial ventures implemented to react to the crisis. Relying on insights from the behavioural theory of the firm and threat-rigidity theory, we explore the antecedents of firms' investments in development of new products and in expansion in international markets and the consequences of these changes on firms' growth performance. Econometric results from a sample of 140 Italian high-tech entrepreneurial ventures support the view that the stock of resources accumulated by larger firms, firms' innovation and internationalization investments in the pre-crisis period and firms' cash flow determine the extent of the two changes. The effects of these changes on firms' short-term growth performance are positive only for investments in development of new products.